Prioritizing a Research Agenda of Transitional Care Interventions for Childhood-Onset Disabilities - Duncan, Andrea; Luong, Dorothy; Perrier, Laure; Bayley, Mark T.; Andrew, Gail; Arbour-Nicitopoulos, Kelly; Chan, Brian; Curran, C. J.; Dimitropoulos, Gina; Hartman, Laura; Huang, Lennox; Kastner, Monika; et al. (Frontiers in Pediatrics, 2021)
Transitional care interventions have the potential to optimize continuity of care, improve health outcomes and enhance quality of life for adolescents and young adults living with chronic childhood-onset disabilities, including neurodevelopmental disorders, as they transition to adult health and social care services. The paucity of research in this area poses challenges in identifying and implementing interventions for research, evaluation and implementation. The purpose of this project was to advance this research agenda by identifying the transitional care interventions from the scientific literature and prioritize interventions for study. A modified-Delphi approach involving two rounds of online surveys followed by a face-to-face consensus meeting with knowledge users, researchers and clinician experts in transitional care (n = 19) was used. A subsequent virtual meeting concluded the formulation of next steps. Experts rated 16 categories of interventions, derived from a systematic review, on importance, impact, and feasibility. Seven of the 16 interventions categories received a mean score rating of ≥7 (out of 10) on all three rating categories. Participants then rank ordered the reduced list of seven interventions in order of priority and the top four ranked interventions advanced for further discussion at a consensus meeting. Using the Template for Intervention Description and Replication (TIDieR) checklist as a guide, the participants identified that a study of a peer system navigator was worthy of future evaluation. This study highlighted that transitional care interventions are complex and multifaceted. However, the presence of a peer to support system navigation, advocacy and individual and family education was considered the most ideal intervention addressing the current gap in care. Future research, which aims to engage patients and families in a co-design approach, is recommended to further develop this intervention.